Comparative assessment of the resilience of new urban settlements to earthquake risk (Case study: Greater Isfahan urban area) - Fazllollah Karimi Ghotbabadi; Ali Zangiabadi (تحقیقات کاربردی علوم جغرافیایی)
Earthquake resilience, defined as the capacity of societies—including social, economic, institutional, geographical, and other dimensions—to withstand and recover from seismic events, is a critical issue that demands attention across various societal contexts. It is essential to acknowledge that attitudes toward resilience and the analytical frameworks employed to assess it significantly influence both the understanding of underlying causes of resilience and the formulation of policies aimed at risk reduction and management. The objective of this study is to evaluate and rank the earthquake resilience of new urban developments within the Isfahan Metropolitan area through the utilization of a combined index. Given the nature of the subject matter, the research adopts a descriptive-analytical approach. The study's statistical population comprises six new urban developments: Shahin Shahr, Majlesi, Sepahan Shahr, Foolad Shahr, Baharestan, and Shahid Keshvari. This research is characterized as applied in nature, and information for the literature review was gathered through library research methods. According to the results derived from the Potentially Optimal Solutions Evaluation Technique (POSET) analysis, the rankings of the urban developments based on the combined index of resilience to earthquake risk are as follows: Majlesi (3), Baharestan (6), Foolad Shahr (7), Sepahan Shahr (8), Shahin Shahr (11), and Shahid Keshvari (14). Consequently, to mitigate the adverse effects of earthquakes on communities, it is imperative to consider the unique capacities of each urban development, thereby reducing potential human and financial losses resulting from such events.